THE ROLE OF MODERN TECHNOLOGIES IN LANGUAGE TEACHING - M. Karimberdiyeva (International Scientific and Current Research Conferences, 2025)
This article discusses the role, advantages and methods of application of modern technologies in language teaching. Several modern technologies used in education are analyzed.